2019
DOI: 10.1111/1365-2664.13495
|View full text |Cite
|
Sign up to set email alerts
|

Linking habitat composition, local population densities and traffic characteristics to spatial patterns of ungulate‐train collisions

Abstract: 1. The total length of railways worldwide exceeds 1 million kilometres and recent railway development directly impacts wildlife because of animal-train collisions.Few studies, however, have analysed factors driving ungulate-train collisions.2. We analysed over 3,500 ungulate-train collisions including roe deer, red deer, wild boar, and moose collected in 2012-2015 in Poland. We compared train traffic characteristics (e.g. traffic intensity, speed, rail curvature), land-use and habitat characteristics (e.g. sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…Track curvature was positively related to mortality at all spatial scales of analysis for bears and at the three smaller spatial scales of analysis for ungulates. Again, this effect is consistent with other studies of wildlife mortality on both roads 50,52 and railways 35,53 . Another set of researchers working in our study area hypothesized that curvature would increase collision risk primarily if it reduces the ability for wildlife to detect approaching trains via acoustic cues 54 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Track curvature was positively related to mortality at all spatial scales of analysis for bears and at the three smaller spatial scales of analysis for ungulates. Again, this effect is consistent with other studies of wildlife mortality on both roads 50,52 and railways 35,53 . Another set of researchers working in our study area hypothesized that curvature would increase collision risk primarily if it reduces the ability for wildlife to detect approaching trains via acoustic cues 54 .…”
Section: Discussionsupporting
confidence: 92%
“…The absence of this effect at smaller spatial scales may reflect the lesser variation in train speed over shorter distances. Several other studies of rail mortality also identified a positive effect of train speed 35,48,49 and vehicle speed is broadly associated with wildlife-vehicle collisions on roads 50 . A plausible explanation for the ubiquity of this relationship is that fast vehicles simply overwhelm the sensory capacity, and hence motor response, of animals 51 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, as of 2011, the numbers of both UVC and fenced road sections started to grow on roads characterized by lower speed and traffic intensity (Figure 4A). Similar to other countries [46,47] this UVC increase can be an effect of increasing wildlife populations in Lithuania [13].…”
Section: Changes In Roadkill and Fencing Patternssupporting
confidence: 64%
“…For example in Spain, there have been increases of 3600% and 300% in UVCs with wild boar and red deer respectively from 2006 to 2012 (Sáenz‐de‐Santa‐Maria & Tellería 2015), and in Sweden, there has been an increase of almost 600% in UVCs with wild boar from 2003 to 2012 (Savberger 2010 in Thurfjell et al 2015). UVCs also include train collisions, which are affected by ungulate density (Jasińska et al 2019) and are increasing in some countries (e.g. Poland, Czech Republic, Hungary), although few studies have been performed regarding this subject (but see Cserkész & Farkas 2013, Kušta et al 2014, Krauze‐Gryz et al 2017).…”
Section: Ungulate‐vehicle Collisionsmentioning
confidence: 99%